Organochlorine Insecticide Contamination in the Inland Ecosystems of Kerala - Rosaland R S (Department of Agricultural Entomology, College of Agriculture, 1995)
Residues of organochlorine insecticides in three different ecosystems Kerala viz., the fresh water ecosystems at Vellayani and Sasthamkotta and backwater region in lower Kuttanad were assessed. Residues in the three components of the ecosystem viz., water, sediment and fishes were estimated. Following were the salient findings. Among organochlorine insecticides (DDT, endosulfan, HCH widely uses) isomers of HCH alone were detected in the samples. The water in all the different regions were found polluted with varying levels of isomers of HCH. The content at different locations in each area did not show statistically significant variation, thus indicating a wide spreading of insecticide contaminants reaching the water boides. The pooled analysis of the data revealed that among the three ecosystems, water in Kuttanad was most polluted and it was followed by Sasthamkotta and Vellayani. The level of pollution is comparable with majority of levels reported from other parts of India so far. The levels of gamma isomer for which 3 ppb has been fixed as the Maximum Residue Limit for drinking purposes, did not reach hazardous levels. But the content of these toxicant in all situations exceeded the ‘safe criterion’ of 0.01 ppb fixed by EPA. Regarding the residues in sediments statistically significant variations did not exit among the locations at Vellayani and Sasthamkotta while at Kuttanad, Moncompu was more significantly polluted than Kumarakom and Pulinkunnu. In pooled analysis of the data Kuttanad and Vellayani were seen on par and more polluted than Sasthamkotta. Taking the residues in water and sediments together the three ecosystems could be ranked in the following descending order of pollution : Kuttanad, Vellayani and Sasthamkotta. Absence of beta and delta residues in water at Vellayani could be due to the settlements of the residues in sediments as shown by a higher proportion of these isomers in sediments at Vellayani than in other ecosystems. Several fold increase of the residue content in sediment compared to those of water revealed that the ‘sediments’ became a ‘sink’ for the pollutants in the ecosystem. Eteroplus suratensis, Heteropneustes fossilis and Macrobrachium rosenbergii (at Kuttanad) and M. idella idella (Vellayani and Sasthamkotta) contain residues of all isomers of HCH. In fresh water ecosystem E. suratensis had highest residue and it was followed by prawn and H. fossilis. In Kuttanad ecosystem H. fossilis was most contaminated and it was followed by M. rosenbergii. At Vellayani the fishes did not contain beta and delta isomers while the prawns contained all the four isomers. This indicated that the former absorbed the pollutant from water and the latter from water and sediments. Significant correlations were lacking between the residue content in fishes and the other components subjected to study in the environment. Residue levels in the animals chosen did not appear to reach hazardous levels. Predominance of beta isomer, known as a chronic toxicant and carcinogen, in the total residue content is alarming. The backwater and freshwater ecosystems in the state were seen polluted with isomers of HCH. Sustained and extensive monitoring of the residues and effective steps for reducing / eliminating the hazard are indicated.